SAT0436 Transjugular renal biopsy: a safe and effective way to perform renal biopsy in systemic lupus erythematosus and antiphospholipid antibody syndrome patients treated with anti-thrombotic drugs – a monocentric experience of 256 procedures. (12th June 2018) - Nielly, H.; Mathian, A.; Cazenave, M.; Izzedine, H.; Haroche, J.; Cohen-Aubart, F.; Rouvier, P.; Brocheriou, I.; Cluzel, P.; Amoura, Z.
Abstract : Background: Renal biopsy is the cornerstone of Lupus nephritis (LN) management. However, transcutaneous renal biopsy (TCRB) is hampered by the antithrombotic treatment frequently prescribed in Systemic Lupus Erythematosus (SLE) and Antiphospholipid Antibody Syndrome (APS). Transjugular renal biopsy (TJRB) offers an attractive alternative for patients at increased risk of bleeding. Objectives: The primary objective of the study was to describe the safety and the diagnostic performance of TJRB in SLE and APS. Methods: A retrospective review of SLE and/or APS patients who consecutively underwent a renal biopsy in our department between January 2004 and October 2016 was performed. Biopsies were divided into four groups: TCRB, TJRB with aspirin treatment (aspirin TJRB), TJRB with anticoagulant treatment (anticoagulant TJRB), and TJRB without anti-thrombotic drug (no-antithrombotic TJRB). Major complications were defined as decease, haemostasis nephrectomy, renal artery embolization, blood transfusion, sepsis and vascular thrombosis. Minor complications were defined as gross haematuria, renal hematoma and arterio-venous fistula. Results: Fifty-four TCRB and 256 TJRB were analysed – 69 aspirin TJRB, 68 anticoagulant TJRB and 119 no-antithrombotic TJRB. Major complications rate was 1.9% for TCRB and 2.0% for TJRB (p=1). One patient in the TJRB group suffering from catastrophic antiphospholipid syndrome (CAPS) died suddenly 6 weeks after the biopsy. No patient died of bleeding complication. One patient in the anticoagulant TJRB group required a renal artery embolization and blood transfusion. Four other patients required blood transfusion (1 in the TCRB group, 1 in the aspirin TJRB group and 2 in the anticoagulant TJRB group). Minor complications rate was 1.9% for TCRB and 7.8% for TJRB (p=0.2). Among the 256 TJRB, the rate of complication (major or minor) was higher for patients with glomerular filtration rate CKD-EPI <30 mL/min (6/24 [25%]) compared to patients with GFR >30 mL/min (16/232 [7%], p<0.01 using the Khi-2 test). Age over 40, blood pressure >140/90 mmHg, APS or positive antiphospholipid biology without APS, Prothrombin Time<50%, activated Partial Thromboplastin Time ratio >1.2, platelets<50 G/L and biopsied kidney size were not associated with a higher rate of complications. The number of glomeruli sampled and the performance of the biopsy to establish a histologic diagnostic were similar in the 4 groups. Conclusions: TJRB provides diagnostic yield and safety similar to those of TCRB. It should be considered as a first intention procedure for SLE and APS patients at risk of bleeding. Disclosure of Interest: None declared